Biofouling inhibition with grafted econea biocide: toward a nonreleasing eco-friendly multiresistant antifouling coating - Regina Ferreira, Olga (2020)
The most effective strategies to control biofouling release toxic and persistent agents into the aquatic environment causing environmental concerns and leading to the implementation of more strict international legislation. This work presents recent progress on an innovative eco-friendly antifouling approach based on the isocyanate-functionalized Econea biocide allowing its chemical fixation in polymeric frameworks, namely, in a foul-release marine coating. The antifouling potential of the generated nonbiocide release coatings for both antimicrobial and long-term marine anti-biofouling applications is reported here for the first time. Inhibition growth effects against Methicillin-resistant Staphylococcus aureus bacterium obtained for Econea-based coatings reveal a decrease in the number of colony forming units (CFUs) up to 5 orders of magnitude in 6 h of exposure when compared to the free bacteria. The growth and the viability profiles (CFU/mL) revealed also bacteriostatic effects. The nonbiocide release coatings were able to minimize considerably the biocide release, becoming 10-fold lower than in a conventional releasing system and providing long-lasting antifouling effects, more than two years, under real seawater conditions. Both antifouling effects follow a nonbiocide release strategy leading to a minimization of the environmental impact of the biocidal coatings and the selective pressure on the microorganisms that evolve treatment resistance.